Estudo comparativo da eficácia instrumental e percebida de um produto cosmético nanotecnólogico para rejuvenescimento facial - Cunha, Andressa (2018)
Topical treatments with nanobiotechnology ingredients represent a non-invasive antiaging method that has been growing heavily in the cosmetic market. For the next few years there is a growth between internal health, beauty and products to prevent and combat aging skin. Innovative conveyors and delivery systems combined with the usual ingredients protect against physical or chemical decomposition affecting percutaneous absorption, thereby increasing the residence time and also penetration into the appendages of the skin. Nanobiotechnology is a branch of nanotechnology that refers to the biological and biochemical application of nanoparticles. It has awakened space for therapeutic disciplines, cosmetics and health care products in the last decades. The objective of this study was to compare the instrumental and perceived efficacy in the treatment of facial aging with a cosmetic product with or without active nanotechnology. This study was conducted in female volunteers aged between 43 and 65 years, who presented an aging degree in the face and neck region, being divided into two groups of 20 volunteers, one with nanotechnological product and the other with the same assets, without nanotechnology. The parameters were: evaluation of instrumental efficacy, image analysis by photographic documentation, questionnaire of perceived efficacy and data analysis. Thus, because the skin presents a biological barrier with unique characteristics, soon being the place of administration and action of assets used in cosmetics, it became necessary to resort to strategies that improve the performance of the active substances at the application site. Thus, it was observed in this research that the nanotechnological formulation presented greater instrumental efficiency compared to the control group, without the presence of nanoparticles, to the following indicators measured length, width and depth of the expression lines in the periocular area in the age range from 51 to 55 years. In this way, it confirms the significant permeation of nanotechnological cosmetics.